Pattern of immunoglobulin and T-cell receptor-δ/γ gene rearrangements in Iranian children with B-precursor acute lymphoblastic leukemia. Issue 5 (July 2014) - Poopak, Behzad; Saki, Najmaldin; Purfatholah, Ali Akbar; Najmabadi, Hossein; Mortazavi, Yosef; Arzanian, Mohammad T.; Khosravipour, Gelareh; Haghnejad, Fariba; Salari, Fatemeh; Shahjahani, Mohammad
Abstract : Introduction: Acute lymphoblastic leukemia (ALL) cells have unique rearranged immunoglobulin heavy chain (IgH), immunoglobulin light chain (IgK), and T-cell receptor (TCR) genes, which can be used as markers for clonality assay and evaluation of minimal residual disease. In this study, we have evaluated the pattern of IgH, IgK chains, and TCRG/D gene rearrangements in precursor-B ALL. Materials and methods: In our prospective study, hyper-variable regions (CDRI and III) of IgH, TCRD (Vδ2–Dδ3 and Dδ2–Dδ3), TCRG (Vγ, VγI, and VγII), and IgK (Vκ-Kde) were studied in 126 cases with diagnosis of B-precursor ALL. Results: One hundred and fourteen (90.5%) out of 126 patients had clonal rearrangements of IgH using consensus primers for CDRI and/or CDRIII regions. Monoclonal, biclonal, and oligoclonal patterns were observed in 63 (57.8%), 38 (34.9%), and 6 (5.5%) patients with IgH (CDRIII) rearrangements, respectively. Clonal rearrangements of TCRG (Vγ) and VγI/II were present in 79.3 and 64.9% of patients, respectively, and only 5% of cases showed biclonal pattern. The VγII rearrangement was the most common (46.8%) type in TCRG. Vδ2–Dδ3 and Dδ2–Dδ3 partial gene rearrangements were observed in 47 (45.2%; n  = 104) and 11 (16.6%; n  = 66) patients, respectively. Biclonal/oligoclonal patterns were present in 13 (27.7%) and 2 (4.3%) cases with Vδ2–Dδ3 rearrangement, respectively. Only one patient had biclonal Dδ2–Dδ3 rearrangement. Clonal pattern of IgK-Kde was detected in 59 cases (67%; n  = 88). Conclusion: Our findings showed that clonal rearrangements of IgH and TCRD (Vδ2–Dδ3 and Dδ2–Dδ3) genes had similar patterns to other studies. Frequency of TCRG (VγI and VγII) and IgK rearrangements was found to be slightly higher than previous reports. Among the IgK rearrangements, VKI (25%) was the most common.